Complexity and Memory: Financial Related Issues Among HBCUs - Shropshire, Kenneth L. (Journal of Intercollegiate Sport, 2013)
The purpose of this paper is to offer a response to Johnson’s (2013) comments. The author offers a defense of the important role Historically Black Colleges and Universities have historically played and continue to do so today.